Out of fear: the role of translated propaganda in Salazar's regime - Chumbo, Isabel (2017)
Fear has shaped discourse along time and has adopted specific characteristics in particular periods of time, whether ruled by religious or political beliefs. The narrative of fear against these regimes has frequently assumed a voice of courage. This can be seen, for instance, among the works of many exiled Portuguese authors - journalists, critics, feminist writers – during the 20th century dictatorship. However fear also emerges from within the regime itself. The need for acceptance among peer countries in Europe has created a translating industry born within the regime whose need for security in terms of political image and propagandistic needs urged the production of numerous translations of political speeches into several languages. Targeting these languages and their cultures made the Estado Novo regime think about specific line-ups built upon the original speeches by Oliveira Salazar. This means that each country was approached differently based upon the same set of Portuguese speeches and that language was a tool kit used for political purposes. This paper will firstly analyse the role of the translated propaganda during the dictatorship, focusing specifically on the decades under Salazar’s rule. Then it will focus on the volume Doctrine and Action, a compilation of 23 speeches published in London by Faber and Faber. Since the narrative of fear is more than just semantics this work will provide an insight into the role of omissions in the translation of these speeches when comparing them with the original ones. The choice of the translators served very specific purposes and was not naïve at all. Para-texts will therefore be analysed in order to show how translators, omissions in the texts, as well as the choice of the speeches, had a very specific purpose, which nowadays could be named an official language policy.